Three new species of Tuberepyris Lanes et Azevedo (Hymenoptera, Bethylidae), with amended diagnosis of the genus - Azevedo, Celso O.; Mugrabi, Daniele F. (Zootaxa, 2014)
Three new species of the Afrotropical Tuberepyris are described and illustrated, T. nihilus Azevedo et Mugrabi, sp. nov. (Madagascar), T. codex Azevedo et Mugrabi, sp. nov. (South Africa), and T. hamus Azevedo et Mugrabi, sp. nov. (Central African Republic). The male of Tuberepyris is described for the first time. T. basibrevis Lanes et Azevedo from Tanzania is evaluated and the genus is redefined. A key to species of Tuberepyris is provided.